Pengaruh promosi penjualan dan brand knowledge terhadap minat beli sepeda motor Yamaha - Machmed Tun Ganyang (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2019)
This research aim to determine the effect of sales promotion and brand knowledge on purchase intention of Yamaha motorcycles. This research used quantitative approach and use survey to collect data from 100 respondents who rided Yamaha motorcycles. The sample technique used is purposive sampling. Questionnaire was used for measuring respondent’s response, which was distributed through Google Form to respondents. Analysis of the data use hypothesis testt ( t-test). The result of this research indicates that sales promotion has an effect significantly on purchase intention and brand knowledge has an effect significanly on purchase intention.